2017
DOI: 10.1108/intr-06-2016-0175
|View full text |Cite
|
Sign up to set email alerts
|

A trust-risk perspective on social commerce use: an examination of the biasing role of habit

Abstract: Purpose Social commerce websites have emerged as new platforms which integrate social media features with traditional commerce aspects to enhance users’ purchasing experience. The purpose of this paper is to examine the role of social factors such as trust toward site members in determining users’ trust and risk evaluations, and the role of social commerce use habit in attenuating users’ rational risk and trust considerations for developing purchase intentions. Design/methodology/approach Relying on the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
140
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 113 publications
(124 reference statements)
9
140
0
10
Order By: Relevance
“…Furthermore, SC is a fusion of OSNs and electronic commerce (Busalim & Hussin, ; W. L. Wu & Li, ). The global revenue out of SC may reach USD 80 billion by 2020 (Farivar, Turel, & Yuan, ). OSNs and SC are vigorously helping firms in realizing marketing objectives.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, SC is a fusion of OSNs and electronic commerce (Busalim & Hussin, ; W. L. Wu & Li, ). The global revenue out of SC may reach USD 80 billion by 2020 (Farivar, Turel, & Yuan, ). OSNs and SC are vigorously helping firms in realizing marketing objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the aforementioned behavior deterrents are given less attention from academic researchers. Motivational factors and drivers of SC remained the primary focus of academic fraternity (Farivar et al, ). The extant literature of consumer behavior treated perceived risk as a multidimensional concept which is composed of social, time, financial, physical, performance, and psychological risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The well-set linkage flanked by photo substance and participation may be credited to the entrenched link among going to places of interest and perception creating medium (Pongpaew, Speece et al, 2017), and the popularity of imagery in TMs posts also confirms that TMs identify tourists' inclination for visual content sharing (Farivar, Farivar et al, 2017). The truth that reasonably lengthy posts boost participation may be credited to the piece of information that TMs are apt to turn out information-rich, sequence of events themes in an informal simulated technique for the reason that they are setting out to put in the picture travelers and sightseers.…”
Section: Discussionmentioning
confidence: 84%
“…For instance, found that trust in social media explains %33 of social commerce purchase intention. Another study specifies that perceived commercial risk and trust in website explain %54 of social commerce purchase intention (Farivar et al, 2017).…”
Section: Engagement and Social Commerce Purchase Intentionmentioning
confidence: 99%